Seasonal fluctuations of gastrointestinal nematode egg counts of bovine in the region of Campinas, State of São Paulo, Brazil: occurrence and prevalence of the genera - Fenerich, Flávio Luiz; Oliveira, Sueli Moda de; Vianna, Wilson de Oliveira; Rodrigues, Ferdinando Madureira (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was conducted from March, 1980 to February, 1984. Faecal nematode eggs count and larval cultures from 96 bovines were realized. Monthly two animals, one, four to ten months old and the other six to ten years old, were put to graze on infected pastures. By differential larval counts, the followings genera of nematodes were found: Cooperia, Trichostrongylug, Oesophagostomum, Haemoncus and Bunostomum. The total EPG (egg per gram) data indicated that the peaks occurred during the months of January and August, and that also the maximum temperatures was influential on the EPG. The faecal egg counts showed any difference between the dry and rainy season.